Pengaruh Citra Merek, Kualitas Produk dan Harga terhadap Keputusan Pembelian Produk Skincare SKIN1004 : Studi pada Mahasiswa Fakultas Ekonomi Universitas Asahan - Devi Dwi Ananda; Neni Tri Astuti (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study aims to determine partially and simultaneously Brand Image, Product Quality and Price on Purchasing Decisions of Skincare Products Skin1004. The number of research samples was 96 respondents, namely students of the Faculty of Economics, Asahan University. Quantitative research methods and using multiple linear regression. The results of the t test, the Brand Image variable partially influences Purchasing Decisions with t count (5.495) > t table (1.98580), the Product Quality variable partially influences Purchasing Decisions with t count (2.145) > t table (1.98580), the Price variable does not influence Purchasing Decisions with t count (1.979) < t table (1.98580). The results of the simultaneous F test of the Brand Image, Product Quality, and Price variables have a significant effect on Purchasing Decisions with F count (104,676) > F table (2.70). The coefficient of determination in this study is R Square of 0.766 or 76.6%. This shows that Purchasing Decisions can be explained by the variables Brand Image, Product Quality and Price by 76.6% while the remaining 23.4% is explained by other factors not examined in this study.